Role of protein kinase G on the post-shock mesenteric lymph blockage ameliorating vascular calcium sensitivity - Zi-gang Zhao; Yan-ling Wei; Chun-yu Niu; Yu-ping Zhang; Li-min Zhang; Li-na Jiang (Acta Cirúrgica Brasileira, 2013)
PURPOSE: To investigate the role of protein kinase G (PKG) in blocking post-shock mesenteric lymph (PSML) return ameliorating the calcium sensitivity in hemorrhagic shock rats. METHODS: Male Wistar rats were randomly divided into sham, shock, shock+ligation (shock plus mesenteric lymph duct ligation (MLDL)), shock+drainage (shock plus PSML drainage) groups. After shock (hypotension 40mmHg) for three hours or corresponding times, the superior mesenteric artery (SMA) was taken out for detecting the PKG and phospho PKG (p-PKG) contents, and the vascular rings of SMA were prepared for assaying the calcium sensitivity using an isolated organ perfusion system. RESULTS: The PKG and p-PKG contents of SMA in shock group were significantly increased than that of sham group, and MLDL or PSML drainage reducing the levels of PKG and p-PKG. Meanwhile, the vascular calcium sensitivity in shock group was significantly lower than that of sham group, MLDL or PSML drainage enhanced the calcium sensitivity. After incubating with PKG regulators in shock+ligation and shock+drainage groups, the PKG agonist 8Br-cGMP reduced the contractility of vascular rings to gradient calcium ions and Emax and the PKG inhibitor agonist KT5823 elevated the calcium sensitivity significantly. CONCLUSION: Protein kinase G plays an important role in post-shock mesenteric lymph blockage improving vascular calcium sensitivity.